«Գլխի ծածկոց» հասկացության բառիմաստային դրսեւորումները հայերենի բարբառներում - Լուսինե Ղամոյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Армянские диалекты различаются не только фонетическими и грамматическими особенностями но и словарным запасом. Исследуя смысловые проявления понятия "головной убор" в армянских диалектах, мы заметили, что имена понятий различаются. Это связано не только с языкомышлением, но и с географическими, временными, религиозными и другими факторами. The dialects of Armenian language differ from each other not only by their phonetic and grammatical characteristic features but also by lexical peculiarities. Studying the semantic manifestations of the concept ‘’Head covers’’ in Armenian dialects we notice that the names of those concepts differ dependent not only on the mentality of people but also on geographical, temporal, religious and many other factors.
Keywords: Language and Literature